An in vitro bladder model with physiological dynamics: Vesicoureteral reflux alters stent encrustation pattern - Zheng, Shaokai; Amado, Pedro; Obrist, Dominik; Burkhard, Fiona; Clavica, Francesco (Frontiers in Bioengineering and Biotechnology, 2022)
In vitro models are indispensable to study the physio-mechanical characteristics of the urinary tract and to evaluate ureteral stent performances. Yet previous models mimicking the urinary bladder have been limited to static or complicated systems. In this study, we designed a simple in vitro bladder model to simulate the dynamics of filling and voiding. The physio-mechanical condition of the model was verified using a pressure-flow test with different bladder outlet obstruction levels, and a reflux test was performed to qualitatively demonstrate the stent associated vesicoureteral reflux (VUR). Finally, the setup was applied with and without the bladder model to perform encrustation tests with artificial urine on commercially available double-J stents, and the volumes of luminal encrustations were quantified using micro-Computed Tomography and image segmentation. Our results suggest that, VUR is an important factor contributing to the dynamics in the upper urinary tract with indwelling stents, especially in patients with higher bladder outlet obstruction levels. The influence of VUR should be properly addressed in future in vitro studies and clinical analyses.